The Relationship between Board Diversity of Information and Communication Technology Expertise and Information and Communication Technology Investment: A Review of Literature - Noor, Marjan Mohd; Kamardin, Hasnah; Ahmi, Aidi (International Journal of Economics and Financial Issues, 2016)
Board members with diverse expertise are crucial to supplement the need of the board to oversee the conduct of the management is in line with the shareholders' interests. In relation to the ICT related industry, diverse board with ICT expertise is in need. There are very limited studies have been conducted to investigate the relationship between board diversity of ICT expertise and ICT investment. Thus, this paper provides the literature review on the relationship between board diversity of ICT expertise and ICT investment. It is hoped that this paper provides important guidance and insights to have a clear understanding of the relationship between board diversity of ICT expertise and ICT investment. Keywords: ICT Investment, Board Diversity, ICT Expertise, Firm Performance JEL Classifications: G34, D83, O14